Zinc metalloprotease FgM35, which targets the wheat zinc-binding protein TaZnBP, contributes to the virulence of Fusarium graminearum - Xin-tong Wang; Kou-han Liu; Ying Li; Yan-yan Ren; Qiang Li; Bao-tong Wang (Stress Biology)
Abstract Metalloproteinases are ubiquitous in organisms. Most metalloproteinases secreted by pathogenic microorganisms are also called virulence factors, because they degrade proteins in the external tissues of the host, thereby reducing the host’s immunity and increasing its susceptibility to disease. Zinc metalloproteinase is one of the most common metalloproteinases. In our report, we studied the biological function of zinc metalloprotease FgM35 in Fusarium graminearum and the pathogen–host interaction during infection. We found that the asexual and sexual reproduction of the deletion mutant ΔFgM35 were affected, as well as the tolerance of F. graminearum to metal stress. In addition, deletion of FgM35 reduced the virulence of F. graminearum. The wheat target TaZnBP was screened using a wheat yeast cDNA library, and the interaction between FgM35 and TaZnBP was verified by HADDOCK molecular docking, yeast two-hybrid, Bi-FC, Luc, and Co-IP assays. The contribution of TaZnBP to plant immunity was also demonstrated. In summary, our work revealed the indispensable role of FgM35 in the reproductive process and the pathogenicity of F. graminearum, and it identified the interaction between FgM35 and TaZnBP as well as the function of TaZnBP. This provides a theoretical basis for further study of the function of metalloproteinases in pathogen–host interactions.